Sex Ratio And Size At First Maturity Of Blue Swimming Crab (Portunus pelagicus) Salemo Island Pangkep Regency - Muh. Saleh Nurdin; Syamsu Alam Ali; Dewi Yanuarita Satari (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2016)
Blue swimming crab (Portunuspelagicus) is aeconomical valuable fisheries importantcommodity  due to the high demand and availability jobs created for the fishermen. Due to their high demand blue swimming crab heavily exploited from Salemo Island. This study aimed at comparing the sex ratio and the size at first maturity of blue swimming crab caught in mangrove ecosystems, coral reefs, and seagrass. Sex ratio was analyzed using chi square test and the size at first maturity was analyzed using the Spearman-Karber formula. The results showed the sex ratio ofmales and femalessmall crab caught in every ecosystem is balanced. The size at first maturity of blue swimming crab caught in mangrove, seagrass and coral reefs, each to the male 81,08 mm, 102,36 mm and 102,87 mm in width and size of female 94,54 mm, 83,35 mm, 98,31 mm width. In a reference to government regulations, the blue male swimming crab caught in the coral reef and seagrass ecosystems have yet to size at first maturity is allowed to be captured. Keywords: blue swimming crab, sex ratio,size at first maturity, Salemo Island